Treatment Outcomes of Stereotactic Body Radiotherapy for Early-stage Non-small Cell Lung Cancer and Lung Metastasis - K M.D., Boonyawan; T M.D., Nanna; P M.D., Puataweepong; T M.D., Suwatanapongched (Asian Pacific Journal of Cancer Care, 2024)
Background and rationale: Stereotactic body radiotherapy (SBRT) is a highly precise localized high-dose per fraction radiation treatment used mainly in lung cancer. Despite SBRT’s increasing use, no clear predictive factors of outcome exist. Objectives: To report local control rates, patterns of failure, and incidence of treatment- related toxicity, and to determine factors predicting SBRT outcomes for primary and secondary lung tumors at Ramathibodi Hospital using competing risk analysis. Materials and methods: This retrospective study included all patients diagnosed with primary early non-small cell lung cancer (NSCLC) and lung metastasis in our radiosurgery and radiotherapy database registry between January 2009 and September 2018. Results: Fifty-nine patients (98 lung tumors) were studied; primary NSCLC and lung metastasis were 15.3% and 84.7%, respectively. Median follow-up was 16.8 months. The overall 1-year local control rate was 90.8%. The most common pattern of failure was distant failure (46.9%). The incidence of radiation pneumonitis (RP) grade ≥2 was 9.2%, and one of four patients with an ultra-central tumor developed grade 5 pulmonary toxicity. The predictive factor for local failure was the mean biological equivalent dose (BED) of the planning target volume (PTV), and for RP grade ≥2, the tumor’s maximal diameter. BED PTV mean <100 Gy had higher local failure than BED PTV mean ≥100 Gy (adjusted subdistribution hazard ratio 8.26; 95% confidence interval (CI) 1.76–38.68, p=0.007). Patients with tumors with maximal diameters ≥5 cm compared with those with maximal diameters <5 cm had more RP grade ≥2 (adjusted subdistribution hazard ratio 5.34; 95% CI 1.52–18.69, p=0.009). The overall 1-year survival rate was 73.5%. Conclusions: Local control of lung tumors using SBRT was high with acceptable toxicity. BED PTV mean was a local control predictor. Large tumors correlated with symptomatic RP grade ≥2. SBRT should be used judiciously for ultra-central lung tumors.